Central aortic blood pressure estimation in children and adolescents: results of the KidCoreBP study. Issue 5 (May 2020) - Mynard, Jonathan P.; Goldsmith, Greta; Springall, Gabriella; Eastaugh, Lucas; Lane, Geoffrey K.; Zannino, Diana; Smolich, Joseph J.; Avolio, Alberto; Cheung, Michael M.H.
Abstract : Background: Central aortic SBP (cSBP) may have superior prognostic value compared with peripheral SBP (pSBP), but noninvasive cSBP measurement techniques have not been formally validated in children and adolescents. Method: This study assessed the accuracy of two automated devices and the radial tonometry/transfer function method (RT-TF) for estimating central pressures and pulse pressure amplification (PPA) in this population, with adherence to validation guidelines for central pressure devices. In 69 children/adolescents aged 3–18 years undergoing clinically indicated aortic catheterization, high fidelity ascending aortic cSBP was measured with a micromanometer-tipped wire and compared with values from SphygmoCor XCEL, Mobil-O-Graph (systolic/diastolic calibration, MoG-C1, or mean/diastolic calibration, MoG-C2) and RT-TF. Reference intra-arterial pSBP was derived from the tonometry pulse calibrated to central mean/diastolic pressures. Results: XCEL, MoG-C1 and MoG-C2 overestimated cSBP by 7.9 ± 6.8 mmHg (mean ± SD), 5.7 ± 10.3 mmHg, and 19.1 ± 14.9 mmHg, exceeding the validation cut-off (5 ± 8 mmHg). Brachial pSBP was also overestimated by XCEL (10.9 ± 8.4 mmHg) and Mobil-O-Graph (11.5 ± 12.3 mmHg). By contrast, central and brachial diastolic pressures were underestimated by the automated devices, albeit mostly within acceptable limits; pulse pressures were, therefore, substantially overestimated. Central-brachial PPA (4.5 ± 4.4 mmHg) was overestimated by XCEL (8.7 ± 3.2 mmHg) and MoG-C1 (11.1 ± 6.4 mmHg), but underestimated by MoG-C2 (−3.0 ± 6.6 mmHg). Given accurate pulse calibration, RT-TF achieved acceptable accuracy for cSBP (−0.2 ± 4.6 mmHg) and central-radial PPA (1.9 ± 5.1 mmHg). Conclusion: In conclusion, XCEL and Mobil-O-Graph overestimated pSBP and cSBP in children and adolescents. cSBP can be obtained via the same transfer function used in adults, but accurate pressure pulse calibration is critical. Video Abstracts: http://links.lww.com/HJH/B222 Abstract : Supplemental Digital Content is available in the text